Analysis of Antioxidant Activity and Natural Prebiotic in Gembili Tubers (Dioscorea esculenta) - Asep Dodo Murtado; Ade Vera Yani; idealistuti idealistuti (Journal of Global Sustainable Agriculture, 2025)
Gembili tuber (Dioscorea esculenta) is a local tuber crop that has not yet been optimally utilized, despite its potential as a source of bioactive compounds beneficial to human health. This study aimed to evaluate the phytochemical content as well as the antioxidant and prebiotic activities of the ethanol extract of gembili tuber. Phytochemical analysis was conducted to determine the total phenolic, flavonoid, and saponin contents. Antioxidant activity was evaluated using the DPPH method. The results showed that gembili extract contained high levels of phenolic compounds, flavonoids, and saponins, which contributed to its antioxidant activity, with inhibition values and IC₅₀ comparable to the control. The DPPH assay revealed that the antioxidant activity of gembili tuber extract increased with increasing extract concentration. The IC₅₀ value decreased from 116.7 ± 1.7 ppm at 1000 ppm to 76.4 ± 0.8 ppm at 3000 ppm. The results of this study indicate that gembili tubers have the potential to be a source of prebiotics and natural antioxidants that can be developed as locally based functional food ingredients.